Magistradas negras no Poder Judiciário brasileiro: representatividade, política de cotas e questões de raça e gênero - Gomes, Raiza Feitosa (2018)
The present work has as its purpose to understand how race and gender inequalities exist in Brazilian magistracy, as well as the resistance processes facing these inequalities, from the contributions of black feminism and from the perspective of intersectionality. For this, it was performed the data analysis of the Brazilian magistrates’ profiles available in the Census of the Judiciary, and of the Resolution 203 of CNJ about the racial quotas in judiciary, as well as the qualitative data production through half structured interviews with black magistrates who work in different Brazilian states. The magistrates report their experiences as black women in a mostly male and white environment, pointing the existence of a “veiled racism” in their everyday life and recognize the relevance of the politics of racial quotas. In this way, this research shows the importance of the race and gender diversity in magistracy and in the other spaces of power.